The Analysis Potency of Animal Slaughterhouse Retribution and Its Contribution for Pendapatan Asli Daerah (PAD) Pontianak City - Atria Tiffany Widyaningsih; Sani Sani (Jurusan Akuntansi Politeknik Negeri Pontianak, 2019)
Regional government financing in performing reliable government duties. This need is increasingly perceived by the region especially since the enactment of regional autonomy in Indonesia, which began on January 1, 2001. With the autonomy, the region is encouraged to be creative to find sources of local revenue that can support regional expenditure financing. From various alternative sources of revenue that may be levied by the regions, the Law on Regional Government setting up local taxes and levies has become a reliable source of revenue for the regions. Since 1984 various Laws on Local Government and financial balance between center and its region. Animal Slaughterhouse that has been built is the only existing RPH in Pontianak City so that its existence is needed by the community in the management and provision of meat that is safe, healthy, whole and kosher for the needs of the surrounding population. Animal Slaughterhouse as a slaughtering business in the provision of healthy meat should consider factors related to sanitation in both the RPH environment and the surrounding environment. In addition to producing meat, RPH also produces additional products that can still be utilized and waste. This research will discuss the potential and contribution of animal slaughtering retribution to Pendapatan Asli Daerah (PAD) Pontianak. The method used in this research is descriptive method, that is method by collecting data which then arranged so that can be made conclusion and suggestion with aim to give systematic and accurate description about the object under research. The data collection techniques conducted by the authors are interviews, observation and documentation. Calculation of the potential of animal slaughterhouse based on the amount of slaughter data. In 2014 - 2016 different with the Realization data in the Department of Agriculture, Fisheries and Forestry of Pontianak City, there is a difference in the number of Retributions of Cutting House Year 2014 of Rp559,327,500, and the difference of slaughterhouse levy in 2015 amounting to Rp612.642.500, whereas in the year 2016 the difference of Levies of Slaughterhouse Rp633.320.000. From the interviews this is due to the slaughter of animals on national holidays which are not levied on retribution fees due to deductions done outside the slaughterhouse but the number of slaughters is recorded as the number of how many animals slaughtered. The existing potential should be explored more deeply because it is a source of local revenue that qualified.